The 1st International Online Conference on Infrastructures 2022
DOI: 10.3390/engproc2022017033
|View full text |Cite
|
Sign up to set email alerts
|

Checking IFC with MVD Rules in Infrastructure: A Case Study

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The Cultural Heritage Object is somewhat more ambiguous: the objects could be of type Heritage Building, Cultural Landscape, Urban Heritage (multiple buildings) or Technical heritage (e.g., a bridge). In IFC4.3 these objects could be classified in the IfcFacility class [57]. However, as this class is not yet available in IFC4, we consider the IfcBuilding class to be the most appropriate.…”
Section: Creating Mvd Based On Idmmentioning
confidence: 99%
“…The Cultural Heritage Object is somewhat more ambiguous: the objects could be of type Heritage Building, Cultural Landscape, Urban Heritage (multiple buildings) or Technical heritage (e.g., a bridge). In IFC4.3 these objects could be classified in the IfcFacility class [57]. However, as this class is not yet available in IFC4, we consider the IfcBuilding class to be the most appropriate.…”
Section: Creating Mvd Based On Idmmentioning
confidence: 99%
“…• support for first experimental IFC schema additions for tunnels (Vilgertshofer et al, 2017); • support for PCD and their analysis (Hecht, 2018); • support for IFC Programming Language (IFC-PL) (Amann, 2018); • support for linked data approaches (Beetz et al, 2019); and • support for IFC4x1, IFC4x2, and IFC4x3 candidate versions of the IFC standard during their development (Jaud et al, 2020).…”
Section: Research Projectsmentioning
confidence: 99%
“…The currently running project "IFC Infrastructure Extension Deployment" (Jaud et al 2020b) has brought inconsistencies in the modelling of linear placement within IFC to light. Additionally, multiple issues have been reported by the software vendors participating in the project.…”
Section: Related Workmentioning
confidence: 99%
“…In the course of the deployment activities of IFC Infrastructure Extension Deployment and IFC Rail Phase 2 projects (Jaud et al 2020b), a multitude of problems and issues were reported to the project teams. Among these were questions and concerns about the linear placement concept, which have been included in our study.…”
Section: New Proposalmentioning
confidence: 99%
See 1 more Smart Citation